The influence of dynamic capabilities on strategic management accounting practices and its effect on value creation in government linked companies / Nik Herda Nik Abdullah - Nik Abdullah, Nik Herda (Institute of Graduate Studies, UiTM, 2018)
Greening the logistics services is an eminent factor that could reduce the excessive used of fossil fuel by the logistics industry. In Malaysia, particularly the logistics industry covers all types of transportation mode such as air, land and sea. Besides the positive economic growth, the side effect of logistics activities is a negative externality with a recent issue of the Global Warming is the inevitable growth of Greenhouse gases (GHG). These activities have given an impact to the environment that has caused major catastrophic. This research is to realise the Strategies and Action Plan of Logistics and Trade Facilitation Masterplan (2015- 2020) and 11th Malaysia Plan; Towards a First-World Mentality Nation. Since, inconsistencies in the operation of logistics services between the “green” and “logistics”, thus the logistics players focus on the greener the operation of logistics services. The fact is that “greenness” is a cost-saving strategy in which the logistics players could benefit from Internalization the Social Cost. Green Logistics has been implemented over 40 countries and there are many research related to this study. However, this research is a continuation of current research and focuses on the internalization of the social costs using Game Theory. This research has explored the use of analytical tool of Congestion Game by studying the congestions in the road network. The study of Price of Anarchy for understanding the cost involved in congestion and resolving the congestions in the road network…